Calcium mediated C–F bond substitution in fluoroarenes towards C–chalcogen bond formation. Issue 1 (26th October 2016) - Maity, Pintu; Ahammed, Sabir; Manna, Rabindra Nath; Ranu, Brindaban C.
Abstract : An efficient C–F bond substitution in electron-deficient fluoroarenes by chalcogens has been achieved using calcium chloride. Abstract : A new calcium chloride mediated C–F bond cleavage in electron deficient fluoroarenes followed by functionalisation via C–Se/Te bond formation has been achieved in the absence of any additive/ligand/organometallic reagent. A series of functionalised organo-selenides and -tellurides were obtained in high yields by this procedure. The precise role of calcium and the possible mechanism have been proposed based on DFT analysis.